Observations on dromedary (Arabian camel) and its diseases Mirror of Research in Veterinary Sciences and Animals (MRVSA) Journal homepage: http://mrvsa.com/ E-ISSN 2307-8073; 2520-324X (Print) - Karima Al-Salihi (Mirror of Research in Veterinary Sciences and Animals, 2016)
This article describes some facts regarding the dromedary, its classification, distribution and population in the world. In addition, the diseases of camels and its classification according to OIE is also described. Since, little is known about the health problem of Iraqi camels, this article plays a magnificent role in filling the knowledge gap and drawing attention towards the improvement of camel health care and its management practices. Much emphasis is given to the occurrences of abortion in the herd of camels in Iraq. Subsequently, the authors would like to give more attention to the Iraqi camels herd and enhancement its future and production performances as camels consider as the animals of the future.